Assessing vestibular function using electroencephalogram rhythms evoked during the caloric test - Han, Yutong; Bai, Yanru; Liu, Qiang; Zhao, Yuncheng; Chen, Taisheng; Wang, Wei; Ni, Guangjian (Frontiers in Neurology, 2023)
The vestibular function involves motion perception and maintenance of body balance. The vestibular function examination can provide an important reference for identifying the etiology of patients with related symptoms and subsequent diagnosis and treatment. The vestibular-related cortex is the final part of the formation of vestibular-related symptom perception and has the function of information processing and integration. In current clinical examinations, less attention has been paid to the cortex related to the vestibular system. Therefore, it is of great significance to add a reference to the expression of the cortex level for the assessment of vestibular function. Electroencephalogram (EEG) can supplement cortex level vestibular function evaluation from the perspective of neuroelectrophysiology. This study collected nystagmus and EEG data during the caloric test to assess vestibular function. Four phases were considered according to the vestibular activation status: before activation, activation, fixation suppression, and recovery. In different phases, the distribution and changes of the relative power of the EEG rhythms (delta, theta, alpha, and beta) were analyzed, and the correlation between EEG features and nystagmus was also investigated. Results show that when the vestibule was activated, the occipital region's alpha power increased, and the beta power of the central and the top regions and of the occipital region on the left decreased. The change of alpha and beta rhythms significantly correlate with nystagmus values in left warm stimulation. Our research shows that the relative power change of EEG rhythms can be used to evaluate the vestibular function, which can provide a new perspective on cortical electrophysiology for vestibular function examination.